An Unusual Case of Extranodal Diffuse Large B-Cell Lymphoma Infiltrating Skeletal Muscle: A Case Report and Review of the Literature - Joseph Hatem; Agata M. Bogusz (Hindawi Limited, 2016)
Diffuse large B-cell lymphoma is extranodal in approximately 40% of cases, arising in nearly any organ system. DLBCL involvement of soft tissue and in particular skeletal muscle is extremely rare, comprising less than 1% of all extranodal non-Hodgkin lymphomas (NHL). We report a case of a 79-year-old man that presented with a DLBCL of the left triceps. In particular, we describe an unusual histologic appearance of pseudoglandular structures, resembling adenocarcinoma. We performed a review of lymphoma cases involving skeletal muscle diagnosed at our institution over the past 15 years as well as thorough PubMed review of the literature. We discuss the features of lymphoma involving skeletal muscle as it pertains to clinical characteristics, histologic subtype, tumor localization, diagnostic studies, therapy, and outcome. Finally, we highlight the diagnostic difficulties that can present in these rare and often challenging cases.